The Contribution of Industrial and Organizational Psychology to the Development of Performance Management Systems - Sulistyani, Nuraida Wahyu; Asmidar, Asmidar; Mulyana, Mulyana (PT. Anagata Sembagi Education, 2025)
This study aims to examine the contribution of Industrial and Organizational Psychology (IOP) in developing a more humane, effective, and sustainable performance management system. The approach used is descriptive qualitative, with data collection techniques in the form of in-depth interviews, participant observation, and documentation studies. The results of the study indicate that the integration of IOP principles is able to form a performance management system that not only assesses work achievements quantitatively, but also considers aspects of motivation, perceptions of fairness, two-way communication in feedback, and a supportive work culture. In addition, the psychological approach to performance management has been shown to contribute to reducing resistance to change, improving psychological well-being, and strengthening employee loyalty to the organization. Thus, IOP plays an important role in creating a holistic and adaptive performance management system to the dynamics of modern organizations. This study recommends that organizations be more proactive in integrating IOP principles in the design and implementation of performance management systems to improve work effectiveness and productivity sustainably.